PLAN ESTRATÉGICO PARA LA ASOCIACIÓN DE CAFICULTORES EL PANGUI, DE EL CANTÓN EL PANGUI, PROVINCIA DE ZAMORA CHINCHIPE - González Caamaño, María Elena (2016)
The purpose of the research was to conduct a " “PLAN ESTRATÉGICO PARA LA ASOCIACIÓN DE CAFICULTORES EL PANGUI, DE EL CANTÓN EL PANGUI, PROVINCIA DE ZAMORA CHINCHIPE”. For this, the theoretical framework that served as a guide for development was used , as well as the analytical and descriptive, deductive , inductive and synthetic technical survey methods , partners and the interview was applied to the Administrator and clients of the organization and direct observation ; which were indispensable to process the information of the organization. To analyze the external factors of this study the political, economic , social, technological , ecological and competitive integrated the same variables that are related to the Association, thereby MEFE matrix identify the main opportunities and threats the organization built , giving a figure of 3.34 results indicating that the organization has a high degree of opportunities and give you support through state budgets , international agencies, bargaining power with suppliers, buyers and unmet demand, aspects that guarantee you the Association to continue to develop positively in the industrial sector in which it operates . With regard to internal factors , the functional areas of the organization are analyzed as are the management , production, marketing and accounting, that by lifting this information allowed for the MEFI matrix providing its main strengths and weaknesses , threw a 3.28 figure result determines that the organization has a high degree of strength and quality of products, customers, production partners , a variety of organic certification , among others, taking advantage of them the best way you would be competitive in the market. With the analysis of these elements described above , we proceeded to the construction of the SWOT matrix , in which the strategic objectives are determined : Strategic Objective No. 1: Make a plan to increase the volume of production of coffee and cocoa will cost $ 22,886.00 Strategic Objective No. 2: Conduct a promotional plan to increase future customers within the association that will cost $ 6,000 . 5 Strategic Objective No. 3: Perform a training plan for managers and members of the Association in order to strengthen their administrative expertise and production will cost $ 4,695 . Strategic Objective No. 4 : Make a plan to attract new partners for coffee and cocoa producers which will cost $ 1000 . Strategic Objective No. 5: Make a plan to implement the cultivation of new products in the Association which will cost $ 5,000 . Strategic Objective No. 6: Implement business philosophy, structural organization and functions manual , it will cost $ 100 . The total cost of this Strategic Plan is $ US $ 39,681.00 , being invested value will allow the organization to increase the volume of production and cultivate new products, thereby increasing their income by improving their economic situation and organization members . Finally the conclusions reached with the detailed analysis of the collected information is presented ; and the recommendations that will be raised the directors of the Association of Coffee Growers THE Pangui .